Genes required to maintain telomeres in the absence of telomerase in Saccharomyces cerevisiae - Alotaibi, Mohammad Kdaimes H. (2012)
In the absence of telomerase, Saccharomyces cerevisiae telomeres erode leading to senescence. Rare cells can survive after this stage as they can elongate their telomeres utilizing homologous recombination. Two different types of survivors can be easily distinguished by Southern blot. Type I survivor cells, elongate the telomere by amplifying Y elements and require RAD51, RAD54, RAD55 and RAD57 for establishment. Type II survivors elongate their telomere by amplifying TG1-3 repeats, however, they require the following genes to be established: RAD50, MRE11 and XRS2, RAD59, SGS1 and KU80 in some cases. Both types require the gene RAD52.